Serbian Elections 2016 - Dušan Pavlović (Contemporary Southeastern Europe, 2016)
Elections in Serbia have been held quite often over the past 26 years. Yet, of all elections that have taken place since the introduction of the multiparty system in 1990, the elections held on April 24 2016, were the most confusing. They were held early, but were neither a product of political, nor economic crisis. So why were they necessary?